Propuesta de Programa en Seguridad Humana y Ley 7600 para las edificaciones del Tecnológico de Costa Rica - Sánchez-Leiva, Daniel (Instituto Tecnológico de Costa Rica, 2017)
This project aims to evaluate the general conditions of human security and accessibility to the physical environment at the Tecnológico de Costa Rica (TEC), Cartago; with the objective of generating a program that allows to respond to the main deficiencies found. Specifically, work will be done with the Rectory building, the construction of the building was made 40 years ago, which is why many of the normative requirements of human security and accessibility that currently apply were not contemplated during its design and construction, it is necessary to make adaptations in order to protect the integrity of the occupants in an emergency and to be able to use the infrastructure for much longer, without having any legal problems. For this evaluation, the University Facilities Safety Index (ISUI) tool was used, which showed the deficiencies of the building based on a percentage of compliance and was complemented with checklists related to aspects of human security and accessibility, which considered Items that were not covered in the ISIU tool. Among the main findings is that, in general, there is a structurally robust building, and the risk to which it is exposed is quite small; However, its non-structural component (doors, windows, corridors, ramps, etc.) and its functional component (mechanisms and procedures for action) were found at a low compliance rate, and it is necessary to act on them in a timely manner. Finally, we obtain a program, that contains a plan of action that contemplates engineering and administrative alternatives, that seek to solve in an integral way the deficiencies found during the evaluation and it is expected that in the future it can be replicated in other buildings.
Proyecto de Graduación (Bachillerato en Ingeniería en Seguridad Laboral e Higiene Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Seguridad Laboral e Higiene Ambiental, 2017.
Keywords: Seguridad ocupacional; Planes; Accesibilidad; Construcción; Diseño